Pengembangan E-Modul Fisika Berbasis 3D Pageflip Professional Pada Materi Listrik Dinamis - Berkat Purapande; Miftah; Marungkil Pasaribu; Nurul Kami Sani; Andi Ulfah Khuzaimah (Universitas Garut, 2026)
This study aims to develop and determine the feasibility of a physics e-module based on 3D Pageflip Professional on dynamic electricity material. This research employed a Research and Development (R&D) method using a simplified Borg and Gall model, which includes the stages of identifying potential and problems, data collection, product design, product validation, product revision, and final product development. The subjects of this study were eighth-grade students of SMP Negeri 19 Palu. The research instruments consisted of validation sheets from material experts and media experts, as well as questionnaires on teacher and student responses using a Likert scale. The results showed that the developed e-module obtained a feasibility percentage of 92.06% from material experts and 89.06% from media experts, both categorized as very feasible. The field testing results indicated percentages of 96.42% from teachers and 94.12% from students, categorized as very good. The e-module features an interactive design integrating text, images, animations, and videos to support students in understanding abstract concepts in dynamic electricity. Therefore, the 3D Pageflip Professional-based physics e-module is feasible to be used as an interactive and innovative learning medium.